Generalized compensative weighted averaging aggregation operators. (September 2015) - Aggarwal, Manish
Highlights: Generalization of compensative weighted averaging operator. Various variants of proposed operators presented. Properties of proposed operators investigated. Special cases of proposed operators. Illustration through examples and a case-study. Abstract: The compensative weighted averaging (CWA) operator is generalized to develop a class of powerful generalized compensative weighted averaging (GCWA) operators with a very fine range of compensatory effects. The conventional means are shown to be the special cases of the proposed GCWA operator. A few extensions are investigated by combining GCWA operator with ordered weighted averaging (OWA) and induced OWA (IOWA) operators. An exponential class of aggregation operators such as exponential CWA, exponential OWA and exponential IOWA operators are developed. The usefulness of GCWA operators is shown through several examples and a case-study.